Civil Society in the Prose of The Prophet - Ariyandi Batu Bara (ELITE JOURNAL, 2023)
This paper is motivated by the author's academic anxiety about: first, the degradation of social cohesion in Indonesian society. Indicators regarding this are: the spiritual crisis of modern society and the occurrence of a human tragedy at the Kanjuruhan Stadium, Malang. Second, the other side of the Prophet's prose has not been revealed that the writer sees is not just a mere beauty of words, more than that it has a philosophical concept revealed as an alternative to create a cohesive society. This fact then encourages the writer to look at the problem from a cultural perspective. The purpose of writing this article is to elaborate on the spirit of civil society which is implied in the prose of the Prophet. The approach used is content analysis by using the book of the Prophet as the primary data. Other literature related will be used as a secondary source. The results of the paper: prose of The Prophet teaches about egalitarianism which contains the values ​​of tolerance, harmony, equality, and diversity of religion itself.Keywords: Society, Civil, Prose.